PENGEMBANGAN MEDIA POP UP BOOK INTERAKTIF PEMBELAJARAN IPAS UNTUK MENINGKATKAN MINAT BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SD - Khalimatus Sa'diyyah; Sukamto; Ervina Eka Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students’ learning interest and critical thinking skills in IPAS (Integrated Science and Social Studies) learning, which is caused by the use of less interactive learning media. This research aims to develop an interactive pop-up book media that meets the criteria of validity, practicality, and effectiveness in improving elementary school students’ learning interest and critical thinking skills. The method used in this study is Research and Development (R&D) with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were fourth-grade students. Data were collected through interviews, questionnaires, and tests, and analyzed using a quantitative descriptive approach. The results showed that the developed media had a very high level of validity, with expert validation scores of 86% for media and 98.67% for material, and a very high level of practicality based on teacher responses (98%) and student responses (100%). In addition, the media proved to be effective in improving learning outcomes, as indicated by the increase in the average pretest score from 59 to 87.67 in the posttest. Therefore, the interactive pop-up book media is feasible to be used as an alternative learning medium in IPAS to enhance students’ learning interest and critical thinking skills.